Asymmetric Isochalcogenourea-Catalyzed Synthesis of 3,4-Dihydropyrans via (4+2)-Cycloadditions of Ethyl But-3-ynoate with Michael Acceptors - Hofer, Mario; Piringer, Magdalena; Scheucher, Anna; Vogl, Lukas S.; Waser, Mario (Synlett, 2025)
We herein report the use of ethyl but-3-ynoate as a C2 building block for asymmetric (4+2)-heterocycloadditions with various Michael acceptors. Upon using chiral isochalcogenoureas as Lewis base catalysts, these reactions can be carried out with good-to-excellent control of the regioselectivity, diastereoselectivity, and enantioselectivity.
Keywords: Organocatalysis; Lewis bases; Isochalcogenoureas; Cycloadditions; Alkynes; Heterocycles